2018
DOI: 10.18178/ijiet.2018.8.3.1032
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effect of Cognitive Style in the Field of STEM on Collaborative Learning Outcome

Abstract: Abstract-Due to the rapid development of the Internet and information technology, schools of all levels around the world pay special attention to the talent cultivation in the field of science, technology, engineering and mathematics (STEM). In STEM education, the cultivation of knowledge and skills plays an important part, and teamwork and problem-solving abilities are critical soft skills for the future talent.In teaching practice, individual differences have long been a critical issue and an important refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
2
7
0
2
Order By: Relevance
“…They often ask friends more than asking the teacher. This result is consistent with previous studies by Lu & Lin (2018). Their research about effect collaborative learning and cognitive style showed that in collaborative learning, FD cognitive style not only had more discussion messages, but they were also more active to discuss with one another in the group.…”
Section: International Journal Ofsupporting
confidence: 93%
See 1 more Smart Citation
“…They often ask friends more than asking the teacher. This result is consistent with previous studies by Lu & Lin (2018). Their research about effect collaborative learning and cognitive style showed that in collaborative learning, FD cognitive style not only had more discussion messages, but they were also more active to discuss with one another in the group.…”
Section: International Journal Ofsupporting
confidence: 93%
“…This result corresponds with the theory proposed by Witkin (1977), students with a field-independent cognitive style tend to deal with things in work independently. The behaviors of students with fieldindependent cognitive style rational or indifferent (Lu & Lin, 2018). These students respond to a task tend to lean or rely on the conditions of the self.…”
Section: Discussionmentioning
confidence: 99%
“…In general studies, personal characteristics such as gender, age and education level were mostly used as individual difference; in educational studies, personal cognitive differences such as learning style, teaching style or perceived teaching style were focused (Lu & Lin, 2012;Lin, Lu & Fan, 2014). Several scholars also discovered that different cognitive styles would affect their learning behaviors in their studies [5]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…3) Are cognitive process patterns of learners of "FI Group" Riessman (1964) categorized cognitive styles into visual, auditory and kinesthetic according to sensory modalities [10]; Gregorc (1977) categorized them into concrete sequential, abstract random, abstract sequential and concrete random based on thinking patterns [11]. Witkin (1964) brought up field-independent (FI) and field-dependent (FD) based on the theory of psychological differentiation; it was widely applied in academic studies [5], [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu dimensi gaya kognitif yang luas dieksplorasi dan telah memiliki aplikasi luas untuk masalah pendidikan adalah dimensi field dependent (FD) dan field independent (FI) (Lu & Lin, 2018). Individu dengan gaya kognitif FD dan FI memiliki perbedaan dalam metode memproses informasi.…”
Section: Pendahuluanunclassified